ENHANCING METACOGNITIVE AND CREATIVE THINKING SKILLS IN CHEMISTRY EDUCATION: THE ROLE OF COLLABORATIVE PROJECT-BASED LEARNING AND STUDENT RESPONSIBILITY - Muhammad Farhan Ivan Phalosa; Rusly Hidayah; I Wayan Dasna; Parlan; Nazriati (JCER (Journal of Chemistry Education Research), 2026)
The integration of metacognitive and creative thinking skills plays a crucial role in equipping STEM students with the necessary competencies to address complex, real-world challenges. This quasi-experimental study investigates the effectiveness of Collaborative Project-Based Learning (CPjBL) supplemented with Electronic Worksheets (E-LKM) in enhancing these essential skills among undergraduate chemistry students (N=52), while examining the moderating effect of student responsibility. The research employed a comparative approach between CPjBL and Project-Based Learning (PjBL) methodologies. Results demonstrated that CPjBL significantly outperformed conventional PjBL in developing both metacognitive skills (with an N-Gain of 0.76 compared to 0.66) and creative thinking abilities (N-Gain of 0.87 versus 0.70). Notably, the benefits were particularly pronounced among students exhibiting high levels of personal responsibility (p < 0.05). Further statistical analysis through univariate ANOVA revealed a significant interaction effect between the CPjBL approach and student responsibility (F = 2.084, p = 0.013), indicating that the effectiveness of the collaborative learning method is substantially influenced by learners' degree of accountability. This finding suggests that while CPjBL represents a powerful pedagogical tool, its implementation should consider students' readiness to take responsibility for their learning process. The study provides empirical evidence supporting CPjBL as an effective framework for cultivating 21st-century skills in chemistry education. The findings have important implications for instructional design, highlighting the need to incorporate collaborative, technology-enhanced learning strategies while simultaneously fostering students' sense of responsibility. Additionally, the research underscores the importance of professional development programs to equip educators with the necessary skills to implement these innovative teaching approaches effectively.